A critical examination of key assumptions underlying diversity and social justice courses in social work. Issue 2 (4th May 2019) - Mehrotra, Gita R.; Hudson, Kimberly D.; Self, Jen M.
ABSTRACT: This article examines underlying assumptions of Master of Social Work diversity and social justice courses as sites that embody social work's dual projects of social justice and professionalization. Through a latent content analysis of course syllabi from 27 US-based social work programs, three key assumptions emerged: (1) social workers are members of dominant social groups; (2) cultural competency and anti-oppression are compatible frameworks; (3) self-awareness mitigates oppression. Findings reflect the reification of dominant culture groups in social work and promotion of individual-level skill development over structural change. Implications and recommendations for social work education and future research are discussed.